2018
DOI: 10.1021/acs.est.8b04687
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Temporal Molecular Fractionation of Dissolved Organic Matter at the Iron Oxyhydroxide Interface

Abstract: While the importance of organic matter adsorption onto reactive iron-bearing mineral surfaces to carbon stabilization in soils and sediments has been wellestablished, fundamental understanding of how compounds assemble at the mineral interface remains elusive. Organic matter is thought to layer sequentially onto the mineral surface, forming molecular architecture stratified by bond strength and compound polarity. However, prominent complexation models lack experimental backing, despite the role of such archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 70 publications
(125 reference statements)
7
93
2
Order By: Relevance
“…The presence of Fe(II) at the end of extraction in all anoxic extracts suggested that the higher amount of extracted OM is probably related to microbial Fe(III) mineral reduction and the release of mineralbound OM during mineral dissolution. A correlation between the dissolved organic carbon (DOC) concentration and the amount of Fe(II) in pore water was reported before for sediment samples that were incubated in the dark under anoxic conditions for 14 d (Dadi et al, 2017). In situ monitoring of the DOC flux in pore water of marine sediment or freshwater wetland also suggested an increase in DOC with increasing microbial iron(III) mineral reduction (Burdige et al, 1992(Burdige et al, , 1999Chin et al, 1998).…”
Section: Effects Of Different Organic Matter Extracts On Rate and Extsupporting
confidence: 53%
“…The presence of Fe(II) at the end of extraction in all anoxic extracts suggested that the higher amount of extracted OM is probably related to microbial Fe(III) mineral reduction and the release of mineralbound OM during mineral dissolution. A correlation between the dissolved organic carbon (DOC) concentration and the amount of Fe(II) in pore water was reported before for sediment samples that were incubated in the dark under anoxic conditions for 14 d (Dadi et al, 2017). In situ monitoring of the DOC flux in pore water of marine sediment or freshwater wetland also suggested an increase in DOC with increasing microbial iron(III) mineral reduction (Burdige et al, 1992(Burdige et al, , 1999Chin et al, 1998).…”
Section: Effects Of Different Organic Matter Extracts On Rate and Extsupporting
confidence: 53%
“…The SOM extracted anoxically showed a higher aromaticity, suggesting that the additional organic matter mobilized by reductive dissolution of iron minerals possesses a higher degree of aromaticity. This is in line with findings described by other studies (Gu et al, 1994;Lv et al, 2016;Avneri-Katz et al, 2017;Coward et al, 2019).…”
Section: Effects Of the Presence Of Oxygen On The Amount And Propertisupporting
confidence: 94%
“…This difference could be caused by the higher content of aromatic functional groups in HA than in FA and the resulting differences in sorption properties. OM with higher aromaticity and larger molecular weight was shown to have a higher absorption affinity to ferrihydrite (Lv et al, 2016;Coward et al, 2019). Since our HA extracted under all conditions https://doi.org/10.5194/bg-2019-308 Preprint.…”
Section: Electron Exchange Capacity (Eec) Of Soil Extracts Determinesmentioning
confidence: 99%
“…Our modeled responses to warming thus suggest that one possible explanation for differences in terrestrial C pool responses to warming may be diverse temperature sensitivities of underlying decomposer communities. Nonetheless, a number of additional factors must be taken into consideration when interpreting our results in the context of global climate change, including soil mineral-mediated modulation of the substrate supply (Schimel and Schaeffer, 2012;Coward et al, 2018), plant-microbe feedbacks (Melillo et al, 2011;Sistla et al, 2014;Suseela and Tharayil, 2018), and temporal variation in temperature. Furthermore, we modeled CUE as a somewhat inflexible property of individual taxa rather than as the emergent property of allocation to different, biochemically impor-tant physiological processes that it is (Hagerty et al, 2018).…”
Section: Comparison To Empirical Warming Studiesmentioning
confidence: 99%